Beat the gun - protection against zero-profit imitation - Stefanie Schubert; Peter-J. Jost (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
The recent development of 3D printing raises the issue of how to protect manufacturing firms from product piracy. In this paper, we are interested in potential regulatory requirements to protect firms from falling victim of product piracy and associated quality choices. We employ a game-theoretic model of duopoly competition. One firm offers a high-quality product facing quality-related costs. An imitator views the product and produces an imitation using a low-cost production method as 3D printing. Our results indicate that copy protection by the high-quality firm yields a higher quality than under patent protection. However, the chosen quality level of the high-quality firm is highest in duopoly without protection. Optimal patent protection crucially depends on the underlying objective function. It is only socially optimal if the regulatory authority maximises GDP.
Keywords: L13; L51; O31; 330